2021
DOI: 10.1063/5.0020592
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between charging and roughness on two adjacent mask holes during plasma etching

Abstract: The surface roughness of a mask surface strongly limits the perfect pattern transfer from the mask to the substrate during the plasma etching process, which results in the deformation of etched features and greatly damages the mask pattern. For the understanding and, ultimately, the control of roughness, the interplay between two adjacent mask holes with nanoscale roughness profile under charging effects was investigated based on a reliable modeling framework. This study first verified that two adjacent mask h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Because the roughness can lead to the local imbalance of accumulated positive and negative charges on the surface of a dielectric material, thus, it could be thought of as a tightly-coupled roughness-charging system. There are two types of roughness which are surface roughness and the line edge roughness (LER) and both of which have been already investigated focusing on the relation between the charging with the roughness [4][5][6][7][8][9]. Memos et al [5] studied this issue taking the trench as a target and revealed that on the one hand, the surface charging suppresses the LER, on the other hand, decreasing the LER helps to reduce the charging potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the roughness can lead to the local imbalance of accumulated positive and negative charges on the surface of a dielectric material, thus, it could be thought of as a tightly-coupled roughness-charging system. There are two types of roughness which are surface roughness and the line edge roughness (LER) and both of which have been already investigated focusing on the relation between the charging with the roughness [4][5][6][7][8][9]. Memos et al [5] studied this issue taking the trench as a target and revealed that on the one hand, the surface charging suppresses the LER, on the other hand, decreasing the LER helps to reduce the charging potential.…”
Section: Introductionmentioning
confidence: 99%
“…b) shows the case study. The roughness here is still parameterized as in the same way used in[8,9]. The mask plane is a perfect surface only with rough opening of the hole.…”
mentioning
confidence: 99%